Analisis implementasi Merdeka Belajar pada pembelajaran Bahasa Indonesia di Sekolah Penggerak SMA Negeri 1 Lima Puluh - Naratama Rukmananda Sinaga; Khairun Nisa; Amelia Simanungkalit; Tuti Ariani Nasution; Resmi Resmi (Jurnal Komunitas Bahasa, 2023)
Analysis of the Implementation of Independent Learning in Indonesian Language Learning at Sekolah Penggerak SMA Negeri 1 Lima Puluh. This study aims to determine the differences in the implementation of learning Indonesian using the 2013 curriculum and the independent learning curriculum as well as the results of the implementation of independent learning in the Indonesian language subject at SMA Negeri 1 Lima Puluh. The research method used is descriptive qualitative using triangulation techniques and the validity of the data is obtained from data reduction, data presentation, and drawing conclusions. The results obtained from this study are that there are differences in the implementation of the 2013 curriculum in the application of learning media, and learning methods and in student learning activities that have not been juxtaposed with technology in the 4.0 era. Independent learning applied by the teacher gives freedom (independence) to students in exploring existing knowledge. The obstacles encountered are internal factors from students and external from the scope of the school.